Creative Attitude in Science Learning Model to Improve Creative Thinking Skills and Positive Attitude of Students Towards Science - Julianto Julianto; Wasis Wasis; Rudiana Agustini; Suprayitno Suprayitno; Asri Susetyo Rukmi; Fitria Hidayati; Endah Rahmawati (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
The results of the literature study show that the Problem Based Learning (PBL) and Creative Problem Solving (CPS) models are proven to be able to improve students' creative thinking skills, but also have weaknesses that need to be improved. To complement the weaknesses of the application of the PBL Model and the CPS Model, it is necessary to develop an Innovative Learning Model that can improve students' creative abilities. The CASL (Creative Attitude In Science Learning) model is a learning model that integrates the CPS model with the PBL model in learning activities. The development of the CASL model is supported by the latest learning theories and the empirical foundation of the latest research. The CASL model has five phases, namely: (1) Generating positive attitudes as creative individuals, (2) Organizing creative learning, (3) Guiding creative investigations, (4) Forming positive attitudes in demonstrating scientific creativity, and (5) Attitude evaluation positive and scientific creativity.